A Study of Graphical and Tabular Displays and Their Interaction with Environmental Complexity - Remus, William (Management Science, 1987)
Since most interactive systems use either graphical or tabular displays, this experiment contrasts the effectiveness of the two displays in making the production scheduling decision in low and intermediate levels of environmental complexity. The study concludes that tabular aids outperform the graphical aids in environments with low complexity, replicating an earlier study. In intermediate complexity environments, the graphical aids outperform the tabular aids. These findings may resolve many conflicts in the literature on data displays.